If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15y + -5 + -14y + 2 = 0 Reorder the terms: -5 + 2 + 15y + -14y = 0 Combine like terms: -5 + 2 = -3 -3 + 15y + -14y = 0 Combine like terms: 15y + -14y = 1y -3 + 1y = 0 Solving -3 + 1y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 1y = 0 + 3 1y = 0 + 3 Combine like terms: 0 + 3 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| n^2-4=45 | | 10/6•3/5 | | -13v=-11 | | 2f+7g-7+8g= | | 8rs+9rs+st= | | 7y-11-2y+7=0 | | 2*(3*r)=42 | | 2y+.05x=16 | | -r+1=-5 | | 30+25x=36x-3 | | 2x(3xr)=42 | | -68=-81+m | | 36/(-9)= | | x-(1/8)y=-11 | | 67p+25=350+25P | | 30/(-9)= | | 4af^4-4ak^4=0 | | -144+4x=54-7x | | 1/3(x)=2 | | h=1+-2gk | | -(0.79m+0.227)=-(2.09m+0.838) | | 33x-2=32x+2 | | n-1+2n=-4 | | 18x+7=-5FORX | | 1.2/58 | | 1.2/5.8 | | 27x-3=26x+1 | | 6x/2=33 | | 5x-5=5-5x | | 5x+2=-9 | | -20x^2+17x+24=0 | | 15x=16x-8 |